2013
DOI: 10.1017/s0950268813002884
|View full text |Cite
|
Sign up to set email alerts
|

The influence of school holiday timing on epidemic impact

Abstract: SUMMARYThe impact of reactive school closure on an epidemic is uncertain, since it is not clear how an unplanned closure will affect social mixing patterns. The effect of school holidays on social mixing patterns is better understood. Here, we use mathematical models to explore the influence of the timing of school holidays on the final size and peak incidence of an influenza-like epidemic. A well-timed holiday can reduce the impact of an epidemic, in particular substantially reducing an epidemic's peak. Final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 29 publications
3
21
2
Order By: Relevance
“…Previous work on school holidays during the flu season suggested that a "late holiday" (e.g., occurs later in the epidemic period) reduces total epidemic size while an early holiday reduces the magnitude of the epidemic peak [35]. We observed a temporary dip in flu transmission immediately following the holiday period, which corresponds to other reports of holiday-related slowing of child transmission [21,22].…”
Section: Discussionsupporting
confidence: 83%
“…Previous work on school holidays during the flu season suggested that a "late holiday" (e.g., occurs later in the epidemic period) reduces total epidemic size while an early holiday reduces the magnitude of the epidemic peak [35]. We observed a temporary dip in flu transmission immediately following the holiday period, which corresponds to other reports of holiday-related slowing of child transmission [21,22].…”
Section: Discussionsupporting
confidence: 83%
“…A relatively small number of reinfections were identified in February, which coincided with the school holiday season, reducing contact opportunities among susceptible children. These results agreed with those of Eames et al [35], who suggested the association between holidays and disease epidemics.…”
Section: Discussionsupporting
confidence: 93%
“…The closure provided increased time to prepare a response and learn more about the disease, but the overall epidemic was very similar to what would have happened without the closure. In contrast, evidence suggests that summer holidays altered the final outcome of the pandemic (at least in the UK), significantly reducing the total number of infections by splitting the epidemic into two smaller peaks [13].…”
Section: Introductionmentioning
confidence: 99%